ANALISIS PENGARUH GETOK TULAR ELEKTRONIK PADA CITRA MEREK DAN NIAT BELI ULANG DI TRAVELOKA - Siska Jeanete Saununu (Soso-Q : Jurnal Manajemen, 2019)
Word of mouth is an informal communication among people about information from a brand, product, company or service. With the growth of internet nowadays, word-of-mouth is not only happen in offline media but even more in online media known as electronic word of mouth. Several theories and studies state that electronic word of mouth has an influence on brand image and repurchase intentions.This study aims to analyze the effect of electronic word of mouth on the brand image and repurchase intentions at Traveloka. The samples used in this study are Traveloka’s consumers who are at least 18 years old and have transacted on the website or application of Traveloka at least 1 times in the last 6 months. The results of this study found that electronic word of mouth influences positively and  significantly  on  brand  image and repurchase intentions. Furthermore, the brand image  variable  becomes  the mediation variable in the relationship between the variable of electronic word of mouth and consumer repurchase intention. Keywords: electronic word of mouth, brand image, repurchase intention, traveloka.